Experimental comparison and optimization guidance of R1233zd(E) as a drop-in replacement to R245fa for organic Rankine cycle application. (August 2018) - Yang, Jingye; Sun, Ziyang; Yu, Binbin; Chen, Jiangping
Highlights: A design of extensive operating conditions in experimental comparison. R1233zd(E) was proven as an appropriate substitute to R245fa in current research. Volume ratio dependent curves of expander efficiency well predict the expander. Non-dimensionless indicator for comparison of alternative in heat exchanger. An optimization guidance was proposed for future work. Abstract: The organic Rankine cycle is capable of converting the low-temperature waste heat into electricity. The commonly used working fluid R245fa will be phased out in the near future because of the significant impact to climate change. In that case, a new refrigerant R1233zd(E) with extremely low GWP is proposed as an environmental friendly substitute in this paper. The investigation is processed with four steps: firstly, a thermodynamic analysis was carried out for prior prediction of the applicability of R1233zd(E) as an alternative to R245fa; secondly, an experimental comparison between two refrigerants was implemented under a design of extensive operating conditions; Afterwards, experimental results were presented. Differences in expansion and evaporation procedure based on three non-dimensionless indicators were analyzed; Eventually, a multi-objective optimization guidance involved with aforementioned indicators was proposed. Comparing the maximum cycle thermal efficiency, R1233zd(E) leads to approximately 3.8% higher than R245fa. Comparing the maximum output electrical power, R1233zd(E) leads to 4.5% better than R245fa. R1233zd(E) is proven as an appropriate alternative to R245fa based on current study. Prediction precision of the volume ratio dependent curves of filling factor and isentropic effectiveness are within 1.2% and 2.7%, which can be used to model a certain expander in optimization procedure.